Revitalizing Islamic Education as a Transformative Strategy in Facing the Challenges of Contemporary Cyber Radicalism - Nur Anisa; Nurdin; Adawiyah Pettalongi (Journal of Contemporary Islamic Education, 2026)
Contemporary cyber radicalism is growing massively in the landscape of digital disruption and identity polarization, with religion being instrumentalized in virtual spaces. Exposure to extreme content places the younger generation as a vulnerable group. This condition emphasizes the urgency of revitalizing Islamic Religious Education based on digital literacy, critical thinking, and religious moderation. This study aims to conceptually analyze the strategic role of Islamic Religious Education in responding to cyber radicalism and to formulate a paradigmatic learning construct that is adaptive to the challenges of the digital era. This study uses a qualitative approach with a literature review. Data sources include books, reputable journal articles, policy reports, and academic documents relevant to cyber radicalism and Islamic Religious Education. Data collection techniques were carried out through systematic searching, critical selection, and reference documentation. Data analysis used content analysis and conceptual synthesis techniques, while data validity was maintained through source triangulation and thorough review. The results of the study indicate that the revitalization of Islamic Religious Education needs to be directed towards the integration of religious moderation, the strengthening of ethical digital literacy, and the development of participatory dialogical pedagogy. Conceptually, this transformation contributes to expanding the function of Islamic Religious Education from normative-instructional to formative emancipatory. The implications of this research affirm its theoretical contribution to enriching the paradigm of digital-based Islamic Religious Education and its practical contribution to the formulation of curriculum policies and preventive learning strategies against cyber radicalism.